Quantum gates and Bose-Hubbard models with dipolar systems - Hughes, M (2022)
Ultracold dipolar systems, featuring strong long-range dipole-dipole interactions, have been brought under increasing quantum control over recent years. In this thesis, we study the use of these properties for quantum information processing and simulation of many-body Bose-Hubbard models with off-site interactions. We first investigate robust entangling protocols for polar molecules, finding that shaped microwave pulses provide two-qubit entangling gates based on the dipole-dipole interaction with robustness to experimentally-relevant errors. We then numerically study the ground state properties of hard-core dipolar bosons confined in cylindrical optical lattices, where the curved lattice surface causes the anisotropic dipole-dipole interactions to vary around the ring of the cylinder. This expands the physics of analogous square lattice models due to the cooperation and competition of the interactions in different directions. Finally, we investigate the applicability of the lowest-band dipolar Bose-Hubbard model itself by comparing lattice and continuum methods for small systems of strongly interacting dipolar bosons in optical lattice potentials.